2017
DOI: 10.1007/s00256-017-2700-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of MRI in predicting meniscal tear reparability

Abstract: MRI can be a reliable and accurate tool to predict the reparability of meniscal tears, with higher prediction rates for bucket-handle tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Although the classification tree method described here demonstrated a reasonable degree of accuracy (72%) among the patients in our data set, this degree of accuracy was not improved in comparison with previously described methods. 1,5,14 MRI has been reported to be sensitive and specific for the diagnosis of meniscus tears. 16 One systematic review and meta-analysis of 29 articles showed a pooled weight sensitivity of 93.3% for the diagnosis of medial meniscus tears and 79.3% for lateral meniscal tears.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the classification tree method described here demonstrated a reasonable degree of accuracy (72%) among the patients in our data set, this degree of accuracy was not improved in comparison with previously described methods. 1,5,14 MRI has been reported to be sensitive and specific for the diagnosis of meniscus tears. 16 One systematic review and meta-analysis of 29 articles showed a pooled weight sensitivity of 93.3% for the diagnosis of medial meniscus tears and 79.3% for lateral meniscal tears.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have suggested that 3-T MRI may help eliminate inconsistencies regarding the reported rate of accurately predicting meniscal tear reparability, 1,5,12,14 noting that a higher spatial resolution could help resolve any potential ambiguity experienced during the image review process. To our knowledge, the current study is the first to characterize the use of 3-T MRI exclusively to evaluate meniscus tear reparability and thus significantly contributes to the existing literature on this topic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations